Targeting the β2‐adrenergic receptor increases chemosensitivity in multiple myeloma by induction of apoptosis and modulating cancer cell metabolism. Issue 1 (22nd November 2022) - Satilmis, Hatice; Verheye, Emma; Vlummens, Philip; Oudaert, Inge; Vandewalle, Niels; Fan, Rong; Knight, Jennifer M; De Beule, Nathan; Ates, Gamze; Massie, Ann; Moreaux, Jerome; Maes, Anke; et al.
Abstract: While multi‐drug combinations and continuous treatment have become standard for multiple myeloma, the disease remains incurable. Repurposing drugs that are currently used for other indications could provide a novel approach to improve the therapeutic efficacy of standard multiple myeloma treatments. Here, we assessed the anti‐tumor effects of cardiac drugs called β‐blockers as a single agent and in combination with commonly used anti‐myeloma therapies. Expression of the β2 ‐adrenergic receptor correlated with poor survival outcomes in patients with multiple myeloma. Targeting the β2 ‐adrenergic receptor (β2 AR) using either selective or non‐selective β‐blockers reduced multiple myeloma cell viability, and induced apoptosis and autophagy. Blockade of the β2 AR modulated cancer cell metabolism by reducing the mitochondrial respiration as well as the glycolytic activity. These effects were not observed by blockade of β1 ‐adrenergic receptors. Combining β2 AR blockade with the chemotherapy drug melphalan or the proteasome inhibitor bortezomib significantly increased apoptosis in multiple myeloma cells. These data identify the therapeutic potential of β2 AR‐blockers as a complementary or additive approach in multiple myeloma treatment and support the future clinical evaluation of non‐selective β‐blockers in a randomized controlled trial. © 2022 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of The Pathological Society of Great Britain and Ireland.